An exploration of the epidemiology, quality and methods of systematic reviews of health professional behaviour change interventions - Weir, Michelle (University of Ottawa (Canada), 2010)
This thesis describes the epidemiology, quality and methods of systematic reviews of health professional behaviour change interventions. The epidemiology was explored using descriptive methods and the quality was assessed with the AMSTAR tool. 'Lumping' and 'splitting', which refers to how broad or narrow a systematic review question is framed, was explored by assessing a subset of reviews to see how review authors framed their systematic review question and justified this decision. The results indicate that there has been an increase in the number of systematic reviews published on professional behaviour change interventions, they are dispersed across various literature sources and the reviews were generally of poor quality. Furthermore, many reviews are 'split', with little justification for the authors' choice of research question. The overlapping subject areas in addition to the low methodological quality raise concern about the organization of the field, including redundancy of publications and potential duplication of efforts.
Keywords: Health Sciences, Epidemiology.